ANALISIS PERSEPSI PELANGGAN TERHADAP KUALITAS LAYANAN COFFEE SHOP ASING DAN COFFEE SHOP LOKAL DI TUNJUNGAN PLAZA SURABAYA - SEPTIA PUTRA N, ENDRU (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Some company on service industry absolutely know the importance of know and understand what is customer perception. Customer is people who use product and or service that avaible in society, which for themselves, family, other people, or other creatures and not for sale. Good quality image not based on service supplier eyesight, but based on costumer eyesight or perception. Based on this costumer who consume and enjoy company service, so that they must determined service quality. Costumer perception to service quality is full estimation for service superiority. In service industry, service quality that play important role on give added value on service experience in full estimation. This research have purpose to know the influence customer perception on service quality in foreign coffee shop, to know the influence customer perception on service quality in local coffee shop, to know the difference of customer perception on service quality in foreign coffee shop and local coffee shop. As for research result show that : in foreign coffee shop taritmethic value of customer perception variable (X) in the amount of 5,548 with significant degree in the amount of 0,000 < 0,05 or 5% that show costumer perception (X) have partially significant influence to quality service (Y) foreign coffee shop and quality service can added more selling result from foreign coffee shop so have to keep up and increase so that costumer not disappointed and feel satisfied, in local coffee shop taritmethic value of customer perception variable (X) in the amount of 4,945 with significant degree in the amount of 0,000 < 0,05 or 5% that show costumer perception (X) have partially significant influence to quality service (Y) local coffee shop and sevice quality can increase selling result from local coffee shop so there are some that must to fix, keep up, and increase and the difference of customer perception on service quality in foreign coffee shop and local coffee shop are customer perception on service quality in foreign coffee shop higher than local coffee shop that because of service quality in foreign coffee shop better than local coffee shop. Foreign coffee shop have more experience in serve their costumer and local coffee shop have to try keep increasing their service so can keep compete with foreign coffee shop. Keyword : costumer perception, service quality, foreign coffee shop, local coffe shop